Umbilical Cord Mesenchymal Stem Cells Attenuate Podocyte Injury in Diabetic Nephropathy Rats by Inhibiting Angpltl4/Integrin β3 in the Glomerulus - Shiyuan Liu; Mingyao Meng; Chunkai Huang; Lijia He; Pu Wang; Zhe Tang; Xi Ran; Hui Gao; Yangfan Guo; Yan He; Jian Chen; Haiyan Hu; et al. (Journal of Diabetes Research)
In this study, we investigated the therapeutic effects and mechanisms of umbilical cord mesenchymal stem cells (UCMSCs) in diabetic nephropathy (DN) ZDF (FA/FA) rats. The therapeutic effects were assessed by renal function tests, the urinary albumin–creatinine ratio, PAS staining, electron microscopy, and TGF-β1 expression in renal tissue. Subsequently, podocyte injury in renal tissue was detected by immunofluorescence staining for podocin. To further explore the underlying mechanism, serum Angptl4 levels were measured, and Angptl4, integrin β3, fibronectin, and podocin levels in renal tissue were analysed by Western blotting. In vitro, podocytes are stimulated with high glucose and then treated with UCMSCs, and podocyte activity and the expression of synaptopodin, Angptl4, and integrin β3 were observed. UCMSC significantly improve renal function, pathological injury, and podocyte injury in the ZDF (FA/FA) rats. Western blot revealed increased expression of Angptl4, integrin β3, and fibronectin in renal tissues of the DN group, and UCMSC treatment significantly downregulated those proteins. However, UCMSC showed no effects on serum Angptl4 concentration. Podocin expression in renal tissues was significantly restored by UCMSC treatment. In vitro, podocyte activity was decreased after high glucose stimulation and improved by UCMSC treatment. UCMSC restored the expression of synaptopodin, and Angptl4 and downstream integrin β3 were also inhibited. Our study suggested that UCMSC therapy could improve renal function and renal pathological changes in ZDF (FA/FA) rats. In addition, inhibition of the Angptl4/integrin β3 pathway is the potential mechanism by which UCMSC attenuates podocyte injury in the DN model.